Parental Guidance in Motivating Children at Elementary School on 19 Ketapang - Rahmawati, Novi Rosita (Program Studi Bimbingan dan Konseling Islam, 2022)
The current phenomenon that occurs is the lack of parental control at home over children's learning activities. Most parents are busy with their respective jobs. Parents fully surrender their children's education to the teacher. So that their children's education is less controlled. Parents do not play an active role in supporting children's learning at school, so children rarely do schoolwork. This type of research is qualitative research. This research was conducted in grades III, IV and V with 6 students and 6 parents as subjects. Methods of data collection using interview guidelines and learning motivation scale. The data analysis technique uses descriptive qualitative analysis. The results of the study show that the role of parents in motivating students who excel, has a very high role in motivating student learning by always giving attention and affection and sufficient time for their children. The subject of two underachieved parental roles has a low role in motivating student learning. The third subject is the factors that influence the role of parents in increasing student learning motivation, namely the presence of attention, prizes, punishments, providing school necessities and prizes and sufficient time for underachieving children due to excessive pampering, extraordinary worry and lack of sense Darling.